Validation of the Spatial Hearing Questionnaire. - Tyler RS; Perreau AE; Ji H; Tyler, Richard S; Perreau, Ann E; Ji, Haihong (Ear & Hearing (01960202), 2009)
Objectives: Subjective questionnaires are informative in understanding the difficulties faced by patients with hearing loss. Our intent was to establish and validate a new questionnaire that encompasses situations emphasizing binaural hearing. The Spatial Hearing Questionnaire is a self-report assessment tool with eight subscales representing questions; pertaining to the perception of male, female, and children's voices; music in quiet; source localization; understanding speech in quiet; and understanding speech in noise.Design: The Spatial Hearing Questionnaire, composed of 24 items, is scored from 0 to 100. It was administered to 142 subjects using one or two cochlear implants. Speech perception and localization abilities were measured, and the Speech, Spatial, and Other Qualities questionnaire was completed to evaluate validity of the questionnaire. Psychometric tests were performed to test the reliability and factor structure of the Spatial Hearing Questionnaire.Results: Results showed high internal consistency reliability (Cronbach's alpha = 0.98) and good construct validity (correlations between the Spatial Hearing Questionnaire and other test measures, including the Speech, Spatial, and Other Qualities, were significant). A preliminary factor analysis revealed scores loaded on three factors, representing the following conditions: localization, speech in noise and music in quiet, and speech in quiet, explaining 64.9, 13.0, and 5.3% of the variance, respectively. Most of the questionnaire items (12/24) loaded onto the first factor that represents the subscale related to source localization. Mean scores on the Spatial Hearing Questionnaire were higher for subjects with bilateral cochlear implants than for subjects with a unilateral cochlear implant, consistent with other research and supporting construct validity.Conclusions: The Spatial Hearing Questionnaire is a reliable and valid questionnaire that can be completed independently by most patients in about 10 minutes. It is likely to be a valuable tool for clinicians and researchers to measure spatial hearing abilities.